Automated Extraction of Dose/Volume Statistics for Radiotherapy-Treatment-Plan Evaluation in Clinical-Trial Quality Assurance - Gong, Yutao U. T.; Yu, Jialu; Pang, Dalong; Zhen, Heming; Galvin, James; Xiao, Ying (Frontiers in Oncology, 2016)
Radiotherapy clinical-trial quality assurance is a crucial yet challenging process. This note presents a tool that automatically extracts dose/volume statistics for determining dosimetry compliance review with improved efficiency and accuracy. A major objective of this study is to develop an automated solution for clinical-trial radiotherapy dosimetry review.